2020
DOI: 10.1146/annurev-virology-011620-040628
|View full text |Cite
|
Sign up to set email alerts
|

Abortive Infection: Bacterial Suicide as an Antiviral Immune Strategy

Abstract: Facing frequent phage challenges, bacteria have evolved numerous mechanisms to resist phage infection. A commonly used phage resistance strategy is abortive infection (Abi), in which the infected cell commits suicide before the phage can complete its replication cycle. Abi prevents the phage epidemic from spreading to nearby cells, thus protecting the bacterial colony. The Abi strategy is manifested by a plethora of mechanistically diverse defense systems that are abundant in bacterial genomes. In turn, phages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
268
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(274 citation statements)
references
References 88 publications
5
268
0
1
Order By: Relevance
“…The lack of insertions in neighbouring genes, however, suggested that this region is essential for cell growth, that the transposon is not able to access it [58] or a part of this genomic island was lost following genome sequencing. The remaining symE genes [3][4][5][6] were predicted pseudogenes with none expressed under standard growth conditions and all tolerating transposon insertions (Table 1). In conclusion, there is evidence of expansion and inactivation of symE genes in Serratia, with one being similar to a previously defined SymE system and two potentially being part of novel type II loci.…”
Section: Dynamic Evolution Of Syme Type I Ta Loci Includes Gene Duplimentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of insertions in neighbouring genes, however, suggested that this region is essential for cell growth, that the transposon is not able to access it [58] or a part of this genomic island was lost following genome sequencing. The remaining symE genes [3][4][5][6] were predicted pseudogenes with none expressed under standard growth conditions and all tolerating transposon insertions (Table 1). In conclusion, there is evidence of expansion and inactivation of symE genes in Serratia, with one being similar to a previously defined SymE system and two potentially being part of novel type II loci.…”
Section: Dynamic Evolution Of Syme Type I Ta Loci Includes Gene Duplimentioning
confidence: 99%
“…During abortive infection, phages adsorb but infection is followed by bacterial dormancy or death; hence, phage propagation is inhibited and few, if any, phages are released [1,3]. The phenotypic and descriptive definition of abortive infection has resulted in a diverse set of known Abi systems that have a wide range of molecular mechanisms [3,4]. Some Abi systems function via a two-gene toxin-antitoxin (TA) mechanism, such as ToxIN/AbiQ [5,6] and AbiE [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Although phages are posited as a solution for antibiotic resistance, bacteria can also evolve resistance to phage infection. Bacteria exist in a constant evolutionary battle with phages, and thus have evolved many systems to resist phage infection, including preventing phage binding, restriction modification systems, CRISPR-Cas9 immunity, and abortive infection 14,15 . Given strong selective pressure from a single phage, bacteria often quickly evolve resistance to that phage in laboratory settings 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In a mechanism conceptually analogous to the pathogen-stimulated programmed cell death driven by the innate immune systems of higher organisms (Abedon, 2012), phage infection can be prevented from sweeping across populations, at the cost of the lives of infected cells. These population-level phage defense systems are often grouped under the umbrella term “abortive infection” (Abi) (Labrie et al, 2010; Lopatina et al, 2020) but actually represent diverse mechanisms to prevent phage replication and induce cell death. These include protease-mediated inhibition of cellular translation (Bingham et al, 2000), toxin-antitoxin pairs (Fineran et al, 2009; Pecota and Wood, 1996) and cyclic oligonucleotide signalling (Cohen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%